Granulocyte-macrophage colony-stimulating factor. Sensitive and receptor-mediated regulation by 1,25-dihydroxyvitamin D3 in normal human peripheral blood lymphocytes. - Tobler, A (1987)
We show that 1,25-dihydroxyvitamin D3 (1,25[OH]2D3), the most hormonally active metabolite of vitamin D3, modulates sensitively and specifically both the protein and messenger RNA accumulation of the multilineage growth factor granulocyte-macrophage colony-stimulating factor (GM-CSF). The regulation of GM-CSF expression is seen in both normal human mitogen-activated T lymphocytes and T lymphocytes from a line (S-LB1) transformed with human T cell lymphotropic virus 1 (HTLV-1). In contrast, cells from a HTLV-1 transformed T lymphocyte line (Ab-VDR) established from a patient with vitamin D-resistant rickets type II with undetectable 1,25(OH)2D3 cellular receptors are resistant to the action of 1,25(OH)2D3. Inhibition of GM-CSF expression by 1,25(OH)2D3 can occur independently of interleukin 2 regulation and is probably mediated through cellular 1,25(OH)2D3 receptors. We conclude that 1,25(OH)2D3 may be important in the physiology of hematopoiesis.